2016
DOI: 10.1126/science.aad9822
|View full text |Cite
|
Sign up to set email alerts
|

Term-seq reveals abundant ribo-regulation of antibiotics resistance in bacteria

Abstract: Riboswitches and attenuators are cis-regulatory RNA elements, most of which control bacterial gene expression via metabolite-mediated, premature transcription termination. We developed an unbiased experimental approach for genome-wide discovery of such ribo-regulators in bacteria. We also devised an experimental platform that quantitatively measures the in-vivo activity of all such regulators in parallel, and enables rapid screening for ribo-regulators that respond to metabolites of choice. Using this approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
428
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 305 publications
(450 citation statements)
references
References 58 publications
9
428
1
Order By: Relevance
“…If the respective metabolite is essential for life, this will lead to a growth stop and/or death of the bacterial cell. Several studies have demonstrated that riboswitches are indeed druggable [68,16,4749]. The most prominent investigation employed a phenotypic screen and identified ribocil that acts as a structurally distinct mimic of the natural ligand flavin mononucleotide to repress ribB gene expression and inhibit cell growth [7].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the respective metabolite is essential for life, this will lead to a growth stop and/or death of the bacterial cell. Several studies have demonstrated that riboswitches are indeed druggable [68,16,4749]. The most prominent investigation employed a phenotypic screen and identified ribocil that acts as a structurally distinct mimic of the natural ligand flavin mononucleotide to repress ribB gene expression and inhibit cell growth [7].…”
Section: Resultsmentioning
confidence: 99%
“…Riboswitches have emerged as possible targets for the development of alternative antimicrobial approaches [18]. They are typically located in the 5ʹ noncoding regions of bacterial mRNA and are able to bind specific metabolites to their aptamers with very high selectivity [911].…”
Section: Introductionmentioning
confidence: 99%
“…A bioinformatics analysis predicted a few conserved riboswitches (Moco, FMN, cobalamin, yybP-ykoY element), the characterized Mg 2+ -responsive riboswitch mgtA [39], and 17 additional riboswitch-like elements, indicating that the Yersinia riboswitch-repertoire still remains undiscovered. Recently, a powerful unbiased high-throughput approach for global discovery of riboswitches and attenuators (Term-seq) has been described [40]. The application of the Term-seq approach to Yersinia grown in different growth media or host environments will not only allow a rapid screening for riboregulators which respond to metabolites of choice, it will also enable the discovery of yet unknown virulence-related riboswitches.…”
Section: Riboswitchesmentioning
confidence: 99%
“…The first noncoding RNAs (ncRNAs) in L. monocytogenes were identified by coimmunoprecipitation with Hfq, a small RNA-binding protein required for the activity of small regulatory RNAs in prokaryotes [21] and by an in silico-based approaches [22]. Since then, the use of high-density tiling arrays and RNA deep sequencing provided a picture of the whole L. monocytogenes transcriptome in multiple conditions, allowing the discovery of many regulatory RNAs [23][24][25][26][27][28] and the annotation of hundreds of regulatory RNAs in L.…”
Section: Unconventional Mechanisms Regulating Bacterial Gene Expressimentioning
confidence: 99%
“…The vast majority of antibiotics affecting translation have RNA binding properties and it has been speculated that RNA-based regulation could be involved in antibiotic resistance genes expression. Recently, several antibiotics resistance genes regulated via termination-based ribo-regulators were identified in L. monocytogenes [24]. Indeed, the discovery of ribo-regulators that specifically respond to antibiotics occurred by applying term-seq, a method enabling quantitative mapping of all exposed RNA 3' ends, to L. monocytogenes bacteria grown in the presence or absence of antibiotic, such as lincomycin.…”
mentioning
confidence: 99%